The role of compensation system in improving the quality of educational services (Halabja University as a model) - جميل مريوان مهدي; حبيب الله شاخة وان جمال (Journal of Economics and Administrative Sciences, 2025)
This study deals with the role of compensation system in improving the quality of educational services (University of Halabja as a Model) also our problem was the following question ; What is the role of compensation system in its different dimensions in improving the quality of educational services? And what is the relationship and impact of using the dimensions of the compensation system to improve the quality of educational services? The hypothesis of the research included the correlation and the impacts between the compensation system and its combined variables in the quality of educational services. This was proved through a field study and the distribution of questionnaire forms to (108) sampled individuals. For data fragmentation and analysis, we used mean, standard Deviation, One Way Anova, Correlations, and Regression Factor within the SPSS program in this study. Finally, the study reached major result which confirms a strong relationship between compensation system and improving the quality of educational services. Also, the study reached recommendations to raise the quality of educational services and making improvements in compensation system to prevent employees to search other ways or sources for livelihood.